Room-Temperature Polyol Synthesis of Ag/SiO2 Nanocomposite as a Catalyst for 4-Nitrophenol Reduction - Canh Minh Thang Nguyen; Vinh Tien Nguyen (Advances in Materials Science and Engineering)
We prepared silver nanoparticles (AgNP) embedded in SiO2 using a green polyol approach by conducting the synthesis at ambient temperature and pH. Glycerol solutions of SiO2 and silver nitrate were stirred overnight at room temperature. UV-vis spectra and TEM images of the reaction dispersion and XRD patterns of the centrifuged solid confirmed formation of AgNP (6 ± 2 nm) were embedded in SiO2. AAS showed that, about 50% of initial silver was deposited on SiO2. The presence of SiO2 enhanced the formation of AgNP and the stability of Ag/SiO2 in glycerol. The reason for these findings was probably the ultrasonic-probe dispersion of SiO2 in glycerol, which caused chemical interactions between glycerol and SiO2. Compared to bare AgNP, the AgNP/SiO2 demonstrated higher catalytic activity toward 4-nitrophenol reduction by NaBH4. The highest apparent rate constant was approximately 1.1 ∗ 10−4 s−1, comparable with Ag/SiO2 catalysts prepared using other methods. This study proposes a greener polyol method to synthesize SiO2-supported AgNP catalyst that does not require heating or regulating pH of the reaction mixture. This nanocomposite can be used in catalytic, antimicrobial, sensing, and other applications that are using AgNP/SiO2 synthesized by conventional methods.